Interface cena e tecnologia : composições cênicas mediadas - Martins, Larissa Hobi (2013)
Based on the presupposition that the arts in the West always counted on resources, supports, and devices pertaining to its time context, an reflection is intended regarding the scenic compositions mediated by digital technologies do. Such technologies are inserted in the daily routine, also composing artistic experiments, thus playing a dialogical role with the art/technology intersection. Therefore, the proposal is to investigate what relationships are established in the contemporary theatrical scene from the contagion by digital technologies, aiming at establishing this parallel through a dialogue with the authors discussing the subject, and also based on the group practices having technological resources as a determinant factor in their plays. Furthermore, a reflection should be made on the scene that incorporates or is carried out in intermediatic events, analyzing how digital technologies (re)configure compositional processes of the plays by GAG Phila7, in the city of São Paulo/SP. For such, the dissertation is organized in three sections comprising four moments, to wit: brief overview of the field, contextualization, poetic analysis and synthesis. Qualitative methods are used as the methodological proposal: semi-structure interview, note and document taking (program, website, playing book, disclosure material for advertising text, photographs, and videos). Within the universe of qualitative research, it works with the epistemological perspective of the Gadamer philosophical hermeneutics. The possibilities allowed by the double virtual (Internet/web) generated a type of theater with another material basis and new forms of organization and structure, being possible to perceive that such technological advances and the arts are mutually contaminated, generating a dislocation in the logics of theatrical composition, movement beginning with the artistic vanguards, gradually intensified, thus offering new possibilities of constructions and hybridization of the of the most different possible types. Experiment ―Profanações_superfície de eventos de construção coletiva‖, idealized by Phila7 is inserted in this perspective. Object of the discussion of such research, the experiment works with possible poetics arising from the intersection with the digital technologies, aiming at identifying and problematizing the challenges from the technological evolution and expansion in a scenic context